2012
DOI: 10.1186/1479-5876-10-199
|View full text |Cite
|
Sign up to set email alerts
|

Five novel glucose-6-phosphate dehydrogenase deficiency haplotypes correlating with disease severity

Abstract: BackgroundGlucose-6-phosphate dehydrogenase (G6PD, EC 1.1.1.49) deficiency is caused by one or more mutations in the G6PD gene on chromosome X. An association between enzyme levels and gene haplotypes remains to be established.MethodsIn this study, we determined G6PD enzyme levels and sequenced the coding region, including the intron-exon boundaries, in a group of individuals (163 males and 86 females) who were referred to the clinic with suspected G6PD deficiency. The sequence data were analysed by physical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
1
10
0
1
Order By: Relevance
“…Finding class II variants (<10% normal activity) such as Union, Mediterranean, Santa Maria, and Canton in the very deficient region was expected (4, 7) because our reference interval is 9.9 to 16.6 U/g Hb (median, 13.2). However, 1 older review mentions both class II and III activities for the Canton variant (21), and a more recent article shows a range of activities for Mediterranean heterozygous females similar to what they observed for heterozygous female A− variants (22). The single Asahi variant in our study had a G6PD activity of 4.2 U/g Hb (31% of the reference interval median).…”
Section: Roc Curves For Males (A) and Females (B)supporting
confidence: 81%
“…Finding class II variants (<10% normal activity) such as Union, Mediterranean, Santa Maria, and Canton in the very deficient region was expected (4, 7) because our reference interval is 9.9 to 16.6 U/g Hb (median, 13.2). However, 1 older review mentions both class II and III activities for the Canton variant (21), and a more recent article shows a range of activities for Mediterranean heterozygous females similar to what they observed for heterozygous female A− variants (22). The single Asahi variant in our study had a G6PD activity of 4.2 U/g Hb (31% of the reference interval median).…”
Section: Roc Curves For Males (A) and Females (B)supporting
confidence: 81%
“…[9], reported a 20% prevalence of G-6-PD deficiency in his study in Nigeria. In other parts of Africa, the prevalence of G-6-PD deficiency has been reported to be 22.5% in Congo (Brazzaville), 15.7% in Mali (Bamako), 13.0% in Uganda and 9.0-15.5% in Gabon [15]. The higher number of G-6-PD deficient females compared with the males was unexpected as G-6-PD deficiency has been reported to be sex linked with male preponderance.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be due to variance in the severity of patients’ G6PD deficiency. Previous research has shown variation among patients in clinical settings ranging from asymptomatic to severely anemic . Therefore, further study should use flow cytometry to assess the relationship between the clinical severity of patients’ G6PD deficiency and the number of RBCs positive for Heinz bodies.…”
Section: Discussionmentioning
confidence: 99%